Genre: the learning dilemma. - Fernández Matarrita, Clarita (2013)
This paper presents a learning experience that was carried out as part of the eight grade's Citizen Education curriculum, at Saint Francis College in Costa Rica, between years 2009 and 2012. This experience was possible due to a mixed methodology that allowed to analyze and question the social structures that have built the gender perspective, and the influence of the socializing agents to who these students and their families have been exposed. This sought to generate awareness of the impact of these agents on the construction of their identity. It shows how students recognize the intervention of the socialization process, by using everyday examples, and how these affect their criteria about gender identity.